The Importance of Developing Countries Joining GATT 94 / WTO - Sibagariang, Syah Putra (LOCUS MEDIA PUBLISHING, 2023)
The establishment of the World Trade Organization (WTO) framework signifies a pivotal milestone in aligning member countries' trading regulations with the WTO's provisions. Developing countries' participation in the WTO fosters equitable competition and contributes to global development. WTO agreements offer flexibility for developing nations to adhere to WTO regulations, providing specialized assistance to the least developed countries (LDCs) and trade concessions in line with GATT regulations. Moreover, the WTO ensures predictability in the business environment, encouraging investment, job creation, and fair competition. Its multilateral trading system fosters peace by facilitating constructive conflict resolution between nations, regulating trade through appropriate mechanisms, and reducing tariffs and non-tariff barriers to enhance affordability.